Using the socio-cultural historical perspective as the framework for culturally appropriate practices - Frick, Teran (Kansas State University, 2015)
All children participate in cultural practices that shape development. Meaningful, authentic connections and interactions with adults build the foundation for respectful integration of cultural diversity in the development of early childhood curriculum. The knowledge of how culture develops forms the foundation of cultural inclusion and appropriate practices in the early childhood setting. Cultural development encompasses the physical environment, the relationships built with people within the environment, and the expectations and roles placed on the child by the family, community and society. Culture is the context in which development occurs and directs the manner of development. The socio-cultural historical perspective, developed by Vygotsky (1978) and elaborated on by Rogoff, (2003) provides a framework for defining cultural development as participation and interactions among individuals as well as within the self. Research indicates recognizing and respecting cultural differences, however, remains a challenge for implementation of culturally appropriate practices. This paper reviews the connection between culture and development by applying the socio-cultural historical perspective to early childhood education classroom practices. Strategies for inclusion and culturally appropriate practice provide the focus for the discussion with illustrative examples from Hungary and the Midwestern United States. Implications for educators, administrators, and teacher training professionals are addressed.
Keywords: Early childhood education; Culturally responsive teaching; Cultural diversity; Socio-cultural historical perspective